Scale-Crossing Brokers and Network Governance of Urban Ecosystem Services: The Case of Stockholm - Henrik Ernstson (Ecology and Society, 2010)
Urban ecosystem services are crucial for human well-being and the livability of cities. A central challenge for sustaining ecosystem services lies in addressing scale mismatches between ecological processes on one hand, and social processes of governance on the other. This article synthesizes a set of case studies from urban green areas in Stockholm, Sweden - allotment gardens, urban parks, cemeteries and protected areas - and discusses how governmental agencies and civil society groups engaged in urban green area management can be linked through social networks so as to better match spatial scales of ecosystem processes. The article develops a framework that combines ecological scales with social network structure, with the latter being taken as the patterns of interaction between actor groups. Based on this framework, the article (1) assesses current ecosystem governance, and (2) develops a theoretical understanding of how social network structure influences ecosystem governance and how certain actors can work as agents to promote beneficial network structures. The main results show that the mesoscale of what is conceptualized as city scale green networks (i.e., functionally interconnected local green areas) is not addressed by any actor in Stockholm, and that the management practices of civil society groups engaged in local ecosystem management play a crucial but neglected role in upholding ecosystem services. The article proposes an alternative network structure and discusses the role of midscale managers (for improving ecological functioning) and scale-crossing brokers (engaged in practices to connect actors across ecological scales). Dilemmas, strategies, and practices for establishing this governance system are discussed.